An NF‐κB‐responsive long noncoding RNA, PINT, regulates TNF‐α gene transcription by scaffolding p65 and EZH2. Issue 9 (18th August 2021) - Ye, Mengling; Wang, Cheng; Zhu, Jie; Chen, Mingkai; Wang, Shuhong; Li, Mingxuan; Lu, Yajing; Xiao, Pingping; Zhou, Mengsi; Li, Xiaoqing; Zhou, Rui
Abstract: Long noncoding RNAs (lncRNAs) are central regulators of the inflammatory response and play an important role in inflammatory diseases. PINT has been reported to be involved in embryonic development and tumorigenesis. However, the potential functions of PINT in the innate immune system are largely unknown. Here, we revealed the transcriptional regulation of inflammatory genes by PINT, whose expression is primarily dependent on the NF‐κB signaling pathway in human and mouse macrophage and intestinal epithelial cell lines. Functionally, PINT selectively regulates the expression of TNF‐α in basal and LPS‐stimulated cells. Mechanistically, PINT acts as a modular scaffold of p65 and EZH2 to coordinate their localization and specify their binding to the target genes. Further, a high expression level of PINT was detected in intestinal mucosal tissues from patients with ulcerative colitis (UC). Together, these findings demonstrate that PINT acts as an activator of inflammatory responses, highlighting the importance of this lncRNA as a potential therapeutic target in infectious diseases and inflammatory diseases.